2009
DOI: 10.1111/j.1442-9071.2009.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute retinal necrosis: a case series with clinical features and treatment outcomes

Abstract: Acute retinal necrosis still has poor visual prognosis. Early diagnosis and initiation of treatment may improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 10 publications
7
87
1
1
Order By: Relevance
“…4 In contrast, many studies have found that the overall rate of retinal detachment remains high even in eyes having undergone laser treatment. 4,8,23 Published reports have also suggested that eyes that do not receive laser are more likely to have extensive disease, consistent with a higher risk of retinal detachment. 22,23 Although there is ongoing debate, most reports suggest that prophylactic barrier laser should be attempted in cases where there is limited vitritis and the retina can be visualized.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…4 In contrast, many studies have found that the overall rate of retinal detachment remains high even in eyes having undergone laser treatment. 4,8,23 Published reports have also suggested that eyes that do not receive laser are more likely to have extensive disease, consistent with a higher risk of retinal detachment. 22,23 Although there is ongoing debate, most reports suggest that prophylactic barrier laser should be attempted in cases where there is limited vitritis and the retina can be visualized.…”
Section: Discussionmentioning
confidence: 82%
“…4,8,23 Published reports have also suggested that eyes that do not receive laser are more likely to have extensive disease, consistent with a higher risk of retinal detachment. 22,23 Although there is ongoing debate, most reports suggest that prophylactic barrier laser should be attempted in cases where there is limited vitritis and the retina can be visualized. 4,22,23 Other treatments include systemic corticosteroids, although they have not been proven to improve visual outcomes.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Second eye involvement occurs in approximately a third of patients, typically within 6 weeks, although fellow eye involvement decades following an initial infection have been described [16]. The natural history of ARN is for 75% of affected eyes to progress to retinal detachment [17], the reported rate with intravenous acyclovir being reduced to 20-52% [7,[18][19][20][21]. Most retinal detachments occur within 6 months of presentation [20]: our patients had follow-up examinations longer than 6 months, suggesting that the risk of retinal detachment is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…4 Today, ARN is recognized as being predominantly caused by varicella zoster virus (VZV) and herpes simplex virus types 1 and 2 (HSV-1, HSV-2), with some studies implicating cytomegalovirus (CMV) and Epstein-Barr virus (EBV). [4][5][6][7][8][9] While the diagnosis of ARN is usually straightforward, much controversy surrounds its management. Debate continues on the benefit or otherwise of aspirin, corticosteroids, barrier laser and prophylactic vitrectomy.…”
Section: Introductionmentioning
confidence: 99%